2001
DOI: 10.1103/physrevb.64.035320
|View full text |Cite
|
Sign up to set email alerts
|

Excitons in small hydrogenated Si clusters

Abstract: The excitonic states of four small hydrogenated Si clusters (SiH 4 ,Si 2 H 6 ,Si 5 H 12 , and Si 10 H 16 ͒ are studied using the diffusion quantum Monte Carlo approach. The importance of using accurate guiding wave functions is stressed and we show that the quantum chemical singles-only configuration interaction method and the time-dependent density functional theory within the adiabatic local-density approximation can provide suitable zeroth-order approximations in these systems.Hydrogenated silicon clusters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 27 publications
5
35
0
Order By: Relevance
“…In the film subjected to photodestruction the short segments appear which are consistent with much deeper traps. This conclusion is supported by theoretical calculations made in [17]. Comparison of Fig.…”
Section: Resultssupporting
confidence: 76%
“…In the film subjected to photodestruction the short segments appear which are consistent with much deeper traps. This conclusion is supported by theoretical calculations made in [17]. Comparison of Fig.…”
Section: Resultssupporting
confidence: 76%
“…The quasi particle gaps obtained here are an upper bound to optical gaps, as excitonic effects are not taken into account [87][88][89] and they may expected to be larger than in the bulk, as suggested by quantum Monte Carlo (QMC) calculations. 90 In addition, several other factors contribute to lowering the quasi particle gaps, including surface reconstruction (cf.…”
Section: High Pressure Core Structuresmentioning
confidence: 81%
“…Here we aim to underline that the good agreement with the experimental spectrum obtained at DFT-LDA + LFE level is not surprising. In fact the compensation of self-energy corrections and electron-hole interaction has been predicted theoretically by Delerue et al [25] and observed by Porter and co-workers [26] in zero-dimensional nanomaterials. Moreover it is very well known that the Time Dependent Density Functional Theory [27], within the LDA approximation (TDLDA), is generally very accurate to describe excited states for small zerodymensional systems like molecules and nanoclusters.…”
Section: Low Dimensional Systemsmentioning
confidence: 88%